Autism Spectrum Disorder – Diagnostic Dilemmas in a Boy with a Doubly Disadvantaged Background: Motnja avtističnega spektra – diferencialno diagnostični pomisleki pri fantu z dvojno obremenjujočim okoljem - Gregorič Kumperščak, Hojka (Acta Medico-Biotechnica, 2021)
Purpose: we present a case report on a boy with autism spectrum disorder (ASD) to illustrate the differential diagnostic questions that can emerge when working with such subjects. Case report: ASD is defined with qualitative deficits in social interactions, communications, and interests and activities. In the subject of this report these symptoms are influenced by a doubly disadvantage background. First, the boy belongs to an ethnicity known for its reservedness in communication – not only with strangers but also within their own families. Second, he was further disadvantaged by his specific microfamily environment.Conclusion: a doubly disadvantaged background appears to have interfered with the subject's development; consideration of this background was crucial for understanding his condition
Keywords: autism spectrum disorder; Asperger syndrome; psychotic disorder